Трансформацијата на глобалната финансиска криза (2008-2010) во глобална должничка криза (2011-) - Гоцевски, Елена (Економски факултет, УКИМ, Скопје, 2017)
What started as housing bubble and mortgage crisis in USA, has grown in Global Financial Crisis, which was transformed into Sovereign Debt Crisis. The main causes of these crises were the lack of transparency of the financial system, failures in the regulatory and lack of supervision, especially in the field of financial innovations, credit rating agencies and hedging funds, inadequate bank risk management, and irrational expectations of the market participants. The consequences of the Global Financial Crisis were overwhelming and were not limited on one country, but were spread out in the whole world. The effects from the crisis were transmitted to the financial markets, the world import and export flows, and resulted with decline in the economical growth and increase of the unemployment rates. Government intervention was more than necessary for saving the financial markets and as attempt for getting the countries out of recession. Because of the Global Financial Crisis, many countries were faced with unavoidable need of bailout from IMF, in order to finance their balances. These public debts caused Sovereign Debt Crisis in many countries, especially in Europe. The Sovereign Debt Crisis in Eurozone appeared mainly as a result of the recession derived from the Global Financial Crisis, the money transfer for help of the banks, inadequate public finance management, uncovering the failures of the Eurozone as a monetary union by the financial markets, as well as because of the incompatible and late reactions of the countries as a result of the crisis. As long-term respond to the crisis, the governments had to make changes in their regulatory rules. With the new regulative and the new government reforms, the failures in the system detected during the crisis will be corrected, though it doesn’t mean that there will be no space for new crisis in future.
The transformation of the global financial crisis (2008-2010) in the global sovereign debt crisis (2011-)
Докторска дисертација одбранета во 2017 година на Економскиот факултет во Скопје, под менторство на проф. д–р Михаил Петковски.
Keywords: Global Financial Crisis, lack of transparency, Sovereign debt crisis, regulation, public debt